Socio-demographic profile of poisoning in children admitted to a tertiary hospital - Srinivasa, B S; Manuprakash, S K; Ara, Syeda Saltanat; Kumar, S R; Prasannakumar, D G (Indian Journal of Child Health, 2016)
Background: Childhood poisoning is a significant public health problem and is very important cause of mortality and morbidity in children. The offending substances used vary from place to place. The pattern of poisoning has been changing with new hazards constantly appearing due to the introduction of new drugs and chemicals. Childhood poisoning is usually accidental making poisoning a preventable problem. Objectives: To determine the socio-demographic and clinical profile and outcome of childhood poisoning in a tertiary care hospital. Materials and Methods: This prospective study was done over a period of 2-year in a tertiary care hospital. We studied children <15 years of age who were admitted to our hospital with a history of poisoning. Children with history of food poisoning, snake bite, scorpion sting, and insect bites were excluded from the study. The demographic profile of patients, various substances of poisoning, mode of poisoning, and outcome of admitted children with poisoning were studied. Results: Among 200 children admitted with the history of poisoning, 126 (63%) were boys and 74 (37%) were girls. The majority of the poisoning were accidental in nature and found to be common in the age group of 1-5 years, children from rural areas, and are of lower socio-economic status. Kerosene poisoning was the most common (35%) agent followed by organophosphorus poisoning (11%). 4 children died due to various complications of poisoning. Conclusion: Common household products were found to be the main source of poisoning in younger age groups from rural background, and the majority was accidental in nature. Educational programs toward creating awareness among public are necessary to reduce the incidence of poisoning in children.